Great Days of the Century: 1936. July 18. Prelude to the Spanish Civil War - Dassier, Jean-Claude; Delannoy, Gilles (France ; Canada ; United Kingdom : Vision 7, 1986)
The Spanish Civil War claimed the lives of 600,000 people and destroyed the country. On the battlefields, not only weapons but also ideologies weighed in.
Keywords: Documentary films